THU0075 EARLY VERSUS DELAYED START OF BARICITINIB IN PATIENTS WITH RHEUMATOID ARTHRITIS IN A PHASE 3 TRIAL OF PATIENTS NAÏVE TO METHOTREXATE TREATMENT. (June 2019) - Fleischmann, Roy; Schiff, Michael; Kvien, Tore K.; Gabay, Cem; Durez, Patrick; Cardoso, Anabela; Zhong, Jinglin; Chen, Yun-Fei; Workman, Jennifer; Takeuchi, Tsutomu
Abstract : Background: Baricitinib (bari) is an oral Janus kinase (JAK)1/JAK2 inhibitor approved to treat moderately to severely active rheumatoid arthritis (RA) in adults in over 50 countries including European countries, the US and Japan. In the 52-week (wk) Phase 3 RA-BEGIN study, bari 4-mg alone or in combination with methotrexate (MTX) showed clinical improvements compared to MTX monotherapy for MTX-naïve patients (pts) with early active RA. 1 Objectives: To assess if pts who receive bari monotherapy early attain enhanced clinical, functional and radiographic outcomes compared to pts who initiated MTX and switched to bari at wk 52. Methods: In RA-BEGIN, 588 pts (mean disease duration 1.4 years) were randomized 4:3:4 to MTX, bari 4-mg once-daily, or combination MTX and bari 4-mg. At Wk 52, pts could enter a long-term extension study in which all pts received open-label bari 4-mg. Pts initially randomized to bari-4 mg monotherapy were defined as early-start and MTX pts who switched to bari 4-mg at Wk 52 were defined as delayed-start for this analysis. Change from baseline using mixed model repeated measures and mean scores were assessed for the Simplified Disease Activity Index (SDAI), Clinical Disease Activity Index (CDAI), Disease Activity Score 28-joints–high-sensitivity C-reactive protein (DAS28-hsCRP), Disease Activity Score 28-joints–erythrocyte sedimentation rate (DAS28-ESR), Health Assessment Questionnaire-Disability Index (HAQ-DI), and modified Total Sharp Score (mTSS) to compare early- vs delayed-start groups between Wks 0 and 100 (Wks 52-100 for mTSS). Percent of pts achieving low disease activity (LDA, SDAI ≤11) and remission (SDAI ≤3.3) were also assessed. Results: LDA and remission response rates in the delayed-start group increased from 60% to 78% and 18% to 31%, respectively, within 4 wks after switching to bari 4-mg. Remission rates reached 47% within 1 year after switching, but were not different from the group that initiated bari (Figure 1 ). Similar results were seen for CDAI, DAS28-ESR, and DAS28-hsCRP (only up to Wk 40 for DAS28-ESR) (data not shown). Pts initially randomized to bari 4-mg had significantly greater change from baseline, observed as early as Wk 1 and up to Wk 52, for HAQ-DI than pts treated with MTX (Figure 2 ). After switching to bari, the delayed-start group showed a rapid improvement in HAQ-DI with similar improvement at Wk 56 – 4 wks after switching to bari. Upon initiating bari, there was a reduction in the rate of structural damage; however, delaying initiation of bari for 1 year resulted in numerically higher mTSS. Conclusion: In early MTX-naïve pts, improved clinical, functional, and radiographic efficacy with bari 4-mg vs MTX was observed in most outcome measures up to 52 wks. Switching from MTX to bari at Wk 52 provided a rapid clinical response, allowing the majority of pts to achieve similar results 4 wks post-switch. However, if the goal of therapy is to achieve rapid and sustained control of disease activity, the differences noted here for HAQ-DI and especially structural progression support earlier switch to bari for pts who do not obtain disease control with MTX. Further analysis may be needed to explore prognostic factors, such as hsCRP and disease duration (< or >6 months), baseline erosion, or anti-citrullinated protein antibody positivity, which may help clinicians identify pts who may benefit from earlier treatment with bari. References: [1] Fleischmann, et al. Arthritis & Rheumatol. 2017;69:506-517 Disclosure of Interests: Roy Fleischmann Grant/research support from: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Michael Schiff Consultant for: Abbvie, BMS, Eli Lilly and Company, JJ, UCB, Speakers bureau: Abbvie, BMS, Tore K. Kvien Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB., Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi, Mylan and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi and UCB, Cem Gabay Grant/research support from: Roche, Pfizer, AB2 Bio Ltd, Consultant for: Roche, Pfizer, Lilly, AbbVie, Sanofi, Regeneron, Bristol-Myers Squibb, Novartis, UCB, AB2 Bio Ltd, Debiopharm, Patrick Durez Speakers bureau: Bristol-Myers Squibb, Eli Lilly, Sanofi, Celltrion, Anabela Cardoso Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Jinglin Zhong Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Yun-Fei Chen Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Jennifer Workman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K.